Odpowiedzi

2010-03-02T19:50:33+01:00
A x = 2
b. x = 4 i 1/3
c. x= 8
d x = 13/3
e x = 0
f x = - 10/24
g x = 5
h x = 0
Najlepsza Odpowiedź!
2010-03-02T19:56:57+01:00
A) 2(x+3)=10
2x+6=10
2x=4
x=2
b) 3(x-1)+2=8
3x-3+2=8
3x=9
x=3
c)2(13-x)-9=1
26-2x-9=1
26-2x=10
-2x=-16
x=8
d)3(1-x)+2=-7
3-3x+2=-7
-3x=-12
x=4
e)3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
0=0
f)4(3x+2)+5(2x+3)=-(2x+13)
12x+8+10x+15=-2x-26
22x+23=-2x-26
24x=-49
x=24/49
g)4(x-2)-2(x-4)=5(x+1)-3x
4x-8-2x+8=5x+5-3x
2x=5x+5-3x
2x=2x+5
0=5
h)2(x-4)=2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x=10x+4+8
-8x=12/*-1x
x=-8/12
x=-2/3